Indonesian English teachers’ voices on the revitalization program at vocational schools - Kailani, Ahmad; Rafidiyah, Dina (JEES (Journal of English Educators Society), 2022)
This research reports on the results of an interview study of nine English teachers at vocational schools (VS) in Indonesia. The study aimed to explore English teachers’ voices of the revitalization program at VS’s in Indonesia. The study shed the light on two major issues of English teaching and learning at VS’s concerning revitalization program implementation. The two main themes were the use of specific technology in the language classroom and video mediated language learning in vocational English classroom.The results indicated that most of teachers more preferably used social media for teaching than utilizing a learning management system (LMS). Teachers have used video mediated teaching method for their English classes either self-production videos or a ready-made video from the internet. English for business was also introduced to students to equip them with basic knowledge for a job selection The results have implications for the implementation of revitalization programs in particular the revitalization of vocational English teaching and learning at SMK. HIGHLIGHTS: Most of teachers more preferably used social media for teaching than utilizing a learning management system (LMS) this is because social media is more practical, handy to use, and equipped with sufficient features, such as voice note, video recording, and device mirroring, which enable teachers to build learning engagement with students. Video mediated EFL teaching is an innovative teaching strategy developed by EFL teachers amidst the crisis of Covid 19. The videos are self-made by teachers and ready to use resources from the internet. The integration of technology into EFL classroom at vocational schools is one of the ultimate goals of the revitalization program at vocational schools across Indonesia.